Anis Syazwani Recipient of Puspanita Community Care Award - Siti Nur Azwin, Zulkapri (2022)
PAYA BESAR, 6 November 2022 – B.Eng (Hons.) Civil Engineering graduand, Nur Anis Syazwani, 24, received the Puspanita Community Care Award at the Universiti Malaysia Pahang (UMP) 17th Convocation Ceremony at the UMP Sports Complex Hall.